Uterine endosalpingiosis: Case report and review of the literature - Meilin Yang; Yuqin Li; Mengkun Chen; Jowei Chen; Fu-Tsai Kung (Elsevier, 2019)
Objective: Endosalpingiosis rarely occurs in the uterus. We report a case and review literature to explore its current clinical diagnosis and treatment. Case report: A 31-year-old woman was admitted to the hospital for suspected uterine leiomyoma with cystic degeneration based on ultrasound and magnetic resonance imaging and surgical treatment. Laparoscopy revealed a large cystic mass protruding from the posterior uterine wall. The mass was resected, and a histologic examination showed that the cyst wall was lined with benign fallopian tube-type ciliated epithelium surrounded by normal myometrium, consistent with the diagnosis of endosalpingiosis of the uterus (also known as a Müllerian cyst). Currently, there are 18 cases (including ours) in the literature. Of these, two had a uterine malignancy, one endometrioid endometrial carcinoma, and another cervical adenocarcinoma. The age at diagnosis varied from 31 to 73, with a mean of 47 ± 8. The typical clinical manifestations were a palpable low abdominal mass, abnormal menstrual bleeding, and pelvic pain. Overall, 75% (12 of 16) of patients underwent a total hysterectomy, while 62.5% (10 in 16) had a concomitant bilateral salpingo-oophorectomy for nonmalignancy. No recurrence was reported. Conclusion: We describe the youngest patient with tumor-like uterine endosalpingiosis. The preoperative diagnosis is challenging because of its rarity. Most patients had a hysterectomy with castration, which may have resulted in overtreatment. Awareness of this lesion is necessary for the differential diagnosis of uterine and adnexal tumors. Review of relevant literature has shown a relationship between endosalpingiosis progression and cancer development, indicating an uncertain and complicated pathology. Keywords: Endosalpingiosis, Müllerian cyst, Müllerianosis, Uterus